Kebijakan luar Negeri Indonesia Dalam Mendukung Palestina sebagai Negara Merdeka Pada Masa Pemerintahan Jokowi - Hendra Maujana Saragih (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2018)
The aim of this paper is to explain how serious and sympathy the Government and the people of Indonesia with the Palestinian struggle colonized by Israel and the unilateral claim made by Israel against Jerusalem as the capital. More than that the dominant factor is certainly the humanitarian crisis which is the reason why it needs to continue to support Palestine. Palestine and Egypt became the party that recognized the earliest Indonesian independence in 1945 even though at that time Palestine was not yet a state, it was not yet independent and it was recognized and respected by the Indonesian Government as concrete evidence of Palestinian existence. The Indonesian government's actions for Palestine have at least been announced from Bung Karno administration to President Jokowi today. None of the Indonesian Presidents since the Republic of Indonesia was independent which did not pay more attention to the Palestinian problem and its variants and it all became a concern of the President and his ranks in fighting for independent Palestine during his foreign policy so far